2020
DOI: 10.1155/2020/8867102
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Splitting Experimental Study on Sandstone at Actual High Temperatures under Different Loading Rates

Abstract: The tensile failure of rocks is a common failure mode in rock engineering. Many studies have been conducted on the tensile strength and failure mode of rocks after high-temperature treatment under dynamic loading. However, research on the effects of high temperature on the dynamic splitting tensile characteristics of sandstone at actual high temperatures is lacking. To investigate the dynamic tensile characteristics of rocks at actual high temperatures, split Hopkinson pressure bar (SHPB) test apparatus and hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…The relationships between temperature and the peak radial strain (Ping, Wu, et al, 2020) as well as the maximum absorbed energy are compared in Figures 12 and 13. From Figure 12, it can be seen that the peak radial strain increases with temperature at different strain rates, which is indicative of a transition from brittleness to ductility.…”
Section: Mechanical Properties Of Thermally Damaged Granite Under Dyn...mentioning
confidence: 99%
See 1 more Smart Citation
“…The relationships between temperature and the peak radial strain (Ping, Wu, et al, 2020) as well as the maximum absorbed energy are compared in Figures 12 and 13. From Figure 12, it can be seen that the peak radial strain increases with temperature at different strain rates, which is indicative of a transition from brittleness to ductility.…”
Section: Mechanical Properties Of Thermally Damaged Granite Under Dyn...mentioning
confidence: 99%
“…For this reason, it is necessary to study the dynamic tensile properties and failure characteristics of thermally damaged rocks to facilitate the construction of geothermal systems. Many scholars have conducted impact tests on rock samples using the Split Hopkinson Pressure Bar (SHPB) to study the strength (Hao et al, 2020; Mardoukhi et al, 2017), deformation (Ping, Wu, et al, 2020), and energy dissipation characteristics (Wang et al, 2018; Xu, Kang, et al, 2020) of rock samples subjected to high‐temperature treatment, including thermally treated intact Brazilian disc (BD) samples, cracked straight through Brazilian disc (CSTBD) samples, and notched semicircular bending (NSCB) samples. Because rocks are heterogeneously formed by polymerization of polyphase minerals, the thermal stress produced by thermal expansion of minerals weakens the contact between rock minerals, thus impairing the tensile properties of rocks.…”
Section: Introductionmentioning
confidence: 99%
“…Their study intriguingly suggested that varying impact speeds mitigated the adverse effects of temperature on sandstone strength. Furthermore, Ping et al 9 conducted dynamic compression tests on sandstone under real-time temperature conditions. Their conclusions highlighted the increasing brittleness of sandstone up to 400 °C, followed by a slight transition toward ductility up to 800 °C.…”
Section: Introductionmentioning
confidence: 99%
“…Gao et al [5] carried out 4 grades temperature treatment for Fangshan marble and conducted dynamic compression tests under dry and saturated conditions. Ping et al [6,7] studied the dynamic mechanical energy evolution characteristics of limestone under high temperature and carried out the experimental study on dynamic splitting tensile of high temperature sandstone under different loading rates. Experimental studies on wave characteristics and dynamic mechanical properties of granite after different high temperatures were conducted by the ultrasonic analyzer and SHPB device [8].…”
Section: Introductionmentioning
confidence: 99%